Statin Therapy Among Bariatric Patients: The Impact on Metabolic Outcomes and Diabetes Status - Mendonça, Fernando M; Silva, Maria M; Borges-Canha, Marta; Neves, João S; Costa, Cláudia; Cabral, Pedro M.; Guerreiro, Vanessa; Lourenço, Rita; Meira, Patrícia; Ferreira, Maria J; Salazar, Daniela; Pedro, Jorge; Varela, Ana; Souto, Selma; Lau, Eva; Freitas, Paula; Carvalho, Davide; group, CRIO (Experimental and Clinical Endocrinology & Diabetes, 2022)
Introduction Statin therapy is associated with an increased risk of developing diabetes. Among bariatric patients, the influence of this therapy on various metabolic outcomes, such as diabetes status and its remission, is largely unknown.Methods This was a retrospective study of 1710 patients who underwent bariatric surgery at our hospital between January/2010 and June/2017. We compared patients with and without statin therapy at baseline, 12 and 24 months after surgery regarding statin use and its impact on several clinical and analytical parameters. Multiple linear regression was performed, adjusting differences for age, sex, surgery type, antidiabetic drugs at baseline, hypertension at baseline, LDL cholesterol ˃ 130 mg/dL, weight variation one year after surgery, and age of obesity onset.Results The overall prevalence of statin use was 20.2% before, 13.6% 12 months after surgery, and 15.0% 24 months after surgery. There was a larger reduction in fasting glucose and HbA1c at 12 and 24 months after surgery among statin-treated patients, with the opposite trend for weight reduction and BMI. Statin-treated patients with diabetes had lower diabetes remission rates (45.3 vs 68.5%) 12 months after surgery, with the highest reduction in HbA1c (1.3±1.3 vs −1.1±1.2%; p=0.042), fasting glucose (−40.8±48.8 vs −30.9±41.6 mg/dL; p=0.028), and insulin (−21.7±28.2 vs −13.4±14.2 mIU/L; p=0.039). The proportion of new-onset cases of diabetes was equal between statin-treated vs non-treated individuals at 12 months (1.9%) and 24 months (1.0%) after surgery.Conclusion Bariatric surgery seems to lead to diabetes remission more frequently in patients not treated with statins. A larger reduction was observed in fasting glucose and HbA1c among statin-treated patients. Statin did not contribute to an increased proportion of new-onset diabetes after surgery.
Keywords: Bariatric surgery; Statins; Diabetes Mellitus